Effect of Zn2+ ions on the structure, morphology and optical properties of CaWO4 microcrystals - Almeida, M. A. P.; Lima, J. R. O.; Morila-Santos, C.; Lisboa Filho, P. N. [UNESP]; Siu Li, M.; Longo, E. [UNESP]; Cavalcante, L. S. (Springer, 2014)
The effect of zinc ions (Zn2+) on the structure, morphology and optical properties of (Ca1-x Zn (x) )WO4 microcrystals with (x = 0, 0.01, 0.02, and 0.03) obtained by the microwave-hydrothermal method at 170 A degrees C for 1 h is reported in this letter. These microcrystals were characterized by X-ray diffraction (XRD), Rietveld refinement, energy dispersive X-rays spectroscopy (EDXS) and field emission scanning electron microscopy (FE-SEM) images. The optical properties were investigated by ultraviolet-visible (UV-Vis) diffuse reflectance spectroscopy and photoluminescence (PL) measurements. XRD patterns and Rietveld refinement data indicated that all the (Ca1-x Zn (x) )WO4 microcrystals present a tetragonal structure and a reduction of lattice parameters and unit cell volume occurs with the increase of Zn2+. EDXS data confirms that the elemental chemical composition was achieved for (Ca1-x Zn (x) )WO4 microcrystals. FE-SEM images showed that the replacement of Ca2+ by the Zn2+ promotes a reduction of average crystals size and considerable changes in crystal shape starting from dumbbell-like to decorative ball-like (Ca1-x Zn (x) )WO4 microcrystals. UV-Vis spectra evidenced a small increase in optical band gap values (from 5.72 to 5.76 eV). Finally, PL emission of (Ca1-x Zn (x) )WO4 microcrystals was improved until x = 0.02 due to the presence of defects at medium range and new intermediate electronic levels in the band gap associated to the Zn2+ content.
Keywords: CaWO4; Microcrystals; Zinc; Distortions; Photoluminescence